PENGARUH EFEKTIVITAS APLIKASI E-KINERJA DAN PENGAWASAN KERJA TERHADAP KINERJA PEGAWAI DINAS SOSIAL KABUPATEN LAHAT - Febyola Febyola; Esty Naruliza; Asma Mario; Ria Astriyani (Taksasila Edukasi Insani, 2026)
This study aims to examine and determine whether the effectiveness of the e-performance application and work supervision has an impact on the performance of employees at the Lahat Regency Social Services Office. The data used is quantitative, sourced from 58 employee respondents, with a questionnaire employed as the data collection method. The surveyed data consists of 28 dimensions of variables related to the effectiveness of the e-performance application, work supervision, and employee performance. The data was processed using SPSS version 27 and analyzed using multiple regression. The results indicate that the effectiveness of the e-performance application and work supervision significantly influences the organizational performance of the Lahat Regency Social Services Office. The higher the effectiveness of the e-performance application and work supervision, the more positive the impact on organizational performance, as evidenced by improved employee quality and skills, more advanced innovation, and the utilization of technology to accelerate and simplify work.Keywords:Effectiveness of E-Performance Applications; E-Performance; Employee Performance; Work Supervision